Growth and Mineral Composition of Twelve Different Kinds of Citrus Seedlings used as Rootstocks - HASSABALLA, ISSAM A. (The Libyan Journal of Agriculture, 2023)
Highly significant differences were recorded in growth vigor and in the level of nine nutrient elements, N. P, K, Ca, Mg, Fe, Zn, Mn and Cu, in top and root of 7-month-old seedlings of twelve Citrus species, varieties and hybrids. C. macrophylla, citrumelo 4475, C. volkameriana and sour orange were the most vigorous. They accumulated in their tops and roots the highest content of most of the nutrient elements determined. On the other hand, ‘Orlando’ tangelo, the citranges: ‘Troyer’, ‘Carrizo’ and ‘Uvalda’, and C. taiwanica showed slow growth and poor vigor. The total amount of different nutrient elements in their tops and roots was very low. ‘Cleopatra’ mandarin and the limes, ‘Benzahair’ and “Rangpur’ showed moderate vigor. Their total uptake of different nutrients was around the general average for all Citrus kinds tested. The limitations in interpreting these data were discussed. Calculated means of nutrient elements, as percentage of total ash, revealed probable nutrient imbalances. Exceptionally high or extremely low levels of one or more element as percent of total ash were detected in all Citrus kinds except sour orange. The need for more work, in this direction, is expressed to allow for more critical comparisons.